Corrosion induced by coir fibre in packaging - Sanyal, B.; Saxena, R. S.; Choudhari, J. C.; Sanyal, S. K.; Ramakrishnan, A. S. (Defence Science Journal, 2014)
An interesting case of extensive dezincification of wickless, pressure type oil stove which could be directly traced to the use of defective filling material in packaging was investigated.